Tanshinone I as a novel therapeutic agent targeting von Willebrand factor-binding protein to mitigate Staphylococcus aureus pathogenicity - Shiyu Zhou; Haoyan Zou; Yueshan Xu; Dongbin Guo; Zhengjie Su; Li Wang; Bingmei Wang; Yicheng Zhao; Xiangyang Leng; Yanping Wang (Virulence)
Staphylococcus aureus (S. aureus) is a prevalent pathogen responsible for a wide range of diseases in humans, contributing to both hospital-acquired and community-acquired infections. The von Willebrand factor-binding protein (vWbp) is pivotal for S. aureus pathogenicity because it induces blood coagulation, thereby facilitating bacterial survival and dissemination within the host. Notably, the absence of vWbp does not hinder S. aureus growth, indicating that vWbp is an attractive target for combating S. aureus infections while mitigating the risk of antibiotic resistance. Our findings revealed that tanshinone I significantly inhibited vWbp-induced coagulation without affecting the proliferation of S. aureus. Hemolysis assays confirmed the biocompatibility of tanshinone I, while Western blot analysis, fluorescence quenching, and thermal shift assays (TSAs) demonstrated that tanshinone I does not alter vWbp expression but directly binds to the protein. Molecular docking studies elucidated the interaction mechanism, identifying ARG-479 and GLN-484 as critical residues for tanshinone I binding. Furthermore, in vivo studies demonstrated that tanshinone I reduces lung tissue damage in mice infected with S. aureus, thereby increasing survival rates. Additionally, tanshinone I was tested in greater wax moth larvae and showed similar protective effects. In conclusion, tanshinone I effectively inhibits vWbp, reducing the virulence of S. aureus. This study underscores the potential of tanshinone I as a therapeutic agent against S. aureus infections, offering a novel strategy to combat bacterial infections while decreasing the critical issue of antibiotic resistance.